Comorbidity Assessment Is Essential During COVID-19 Treatment - Jakhmola, Shweta; Indari, Omkar; Baral, Budhadev; Kashyap, Dharmendra; Varshney, Nidhi; Das, Ayan; Chatterjee, Sayantani; Jha, Hem Chandra (Frontiers in Physiology, 2020)
Coronavirus disease 2019 (COVID-19) caused by SARS-CoV2 is associated with various comorbidities; cardiovascular diseases, hypertension, diabetes, liver, lung diseases, and neurological ailments. The majority of the dysfunctions mentioned above are often associated with endothelial deterioration, indicating that endothelium can be the target of SARS-CoV2. Our study is an exclusive observational study that quantitatively analyses COVID-19 related comorbidities. We retrieved the data of % population of COVID-19 hospitalized and deceased patients with associated comorbidities from publicly accessible portals of the five European countries. A two tailed t-test enabled us to determine the significant proportions of deaths compared to hospitalized patients with associated comorbidity. Our study revealed that deaths associated with cardiovascular disease and diabetes are highly significant (p<0.0001) compared to hospitalized in countries like Italy, France, and Spain unlike the Netherlands. Deaths from kidney diseases (Italy- p<0.0001; Sweden- p<0.0001; Netherlands- p=0.0001; France- p=0.0033) and neurological ailments (France- p=0.0001; Netherlands- p<0.0001) are significantly higher than the total hospitalized patients affected by the particular comorbidity. We have noted that deaths due to liver diseases are least associated with COVID-19 among all comorbidities. Intriguingly, immunodeficiency shows mixed outcomes in death proportions compared to the hospital admitted individuals. Besides, the current COVID-19 treatment regime is based on drugs like losartan, ACE inhibitors, angiotensin-receptor blockers, Remdesivir, Chloroquine, Hydroxychloroquine, etc. which may modulate the severity of the comorbidities. These comorbidities can create chaos in the existing healthcare system and may worsen the disease outcome.